2008
DOI: 10.1038/eye.2008.311
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric blepharoptosis: a 10-year review

Abstract: Purpose To examine the characteristics of blepharoptosis and the success of surgical intervention in a large group of children presenting to a specialist at paediatric ophthalmology center. Methods Ten-year retrospective case notes review of patients presenting to the Birmingham Children's Hospital for blepharoptosis surgery. Resultant database was interrogated for aetiology of ptosis; severity; surgical correction; outcome; complications and need for reoperation. Results One hundred and fifty five children (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
4
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 15 publications
1
65
4
4
Order By: Relevance
“…1,2 Frontalis suspension is the most commonly used surgical technique for the correction of severe congenital ptosis with poor levator muscle function ( 4 mm). 3,4 Various surgical designs and different suspension materials have been described and autogenous fascia lata has been considered the goldstandard material. Despite the fact that recent studies showed successful results with frontalis suspension surgery, numerous other studies reported the disadvantages and complications of this surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Frontalis suspension is the most commonly used surgical technique for the correction of severe congenital ptosis with poor levator muscle function ( 4 mm). 3,4 Various surgical designs and different suspension materials have been described and autogenous fascia lata has been considered the goldstandard material. Despite the fact that recent studies showed successful results with frontalis suspension surgery, numerous other studies reported the disadvantages and complications of this surgery.…”
Section: Introductionmentioning
confidence: 99%
“…22 Frontal askı tekniği, levator fonksiyonunun yetersiz olduğu ağır pitozis olgularında, nöromus-küler hastalıklara bağlı pitozislerde, blefarofimozis sendromlu olgularda yaygın olarak kullanılan bir tekniktir. 7 Frontal askı cerrahisinde çok çeşitli askı materyalleri kullanılmakla birlikte ideal askı materyeli konusunda tam bir görüş birliği yoktur. Fasiya lata, kozmetik olarak en iyi sonuç veren, en az komplikasyon ve en az nüks oranı elde edilen askı materyali olarak bildirilmektedir.…”
Section: Discussionunclassified
“…6 Levator cerrahisi ile hem konjenital hem de edinsel pitozis olgularında başarılı sonuçlar bildirilmiştir. [7][8][9] Levator fonksiyonun yetersiz olduğu blefaropitozis olgularında organik veya inorganik maddeler ile frontal askı cerrahisi uygulanmaktadır. Günümüzde askı materyali olarak otojen fasiya lata, donör fasiya latası, ayak ekstansör tendonu, palmaris longus tendonu, poliflament naylon kablo tip sütür, polipropilen, mersilen "mesh", silikon, politetrafluoroetilen gibi maddeler tercih edilmektedir.…”
unclassified
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Harrad and colleagues 2 identified amblyopia in only 17% of children with ptosis. On the other hand, Fiergang and colleagues 1 found amblyopia in 71% of patients with unilateral or asymmetric congenital ptosis severe enough to cause compensatory head posturing; they attributed the amblyopia to deprivation from the ptosis in 80% of amblyopic children.…”
mentioning
confidence: 99%